Sistem Monitoring Kesehatan Karyawan Menggunakan Wemos D1 Untuk Antisipasi Penularan Covid 19 Berbasis Internet Of Things - Nuris Dwi Setiawan; Irene Ongkowijoyo (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
The Covid-19 pandemic has had a negative impact on the economic sector, many companies have laid off employees to reduce transmission, but this has caused a bigger problem. The decline in production levels threatens to make companies lose money, this is responded well by the government by issuing a "New Normal" policy. ” is a policy that allows a company to employ employees with strict health protocols. One of the contents of the protocol is to monitor the body temperature of employees when they enter the company, checking body temperature when entering the company is not enough because there are often employees who suddenly get sick at work, employee health conditions that are not monitored properly will have an impact. further spread of the corona virus. The creation of a real-time employee health monitoring system will help anticipate the transmission of covid-19 detected from body temperature, using the MLX90614 sensor connected to the Wemos D1 microcontroller which is used to manage data from the sensor and send data wirelessly. This device can turn on the buzzer automatically if the employee's body temperature is above the normal body temperature limit to warn the company if the employee's health condition is not good, the tool is packaged in a practical way so that it can be used by employees throughout work and does not interfere with performance, monitoring results obtained will be displayed to the user in real time through the Android Application interface and will be stored in the form of a text file in the database.